1996
DOI: 10.1128/aem.62.12.4465-4470.1996
|View full text |Cite
|
Sign up to set email alerts
|

Development of an arabinose-fermenting Zymomonas mobilis strain by metabolic pathway engineering

Abstract: The substrate fermentation range of the ethanologenic bacterium Zymomonas mobilis was expanded to include the pentose sugar, L-arabinose, which is commonly found in agricultural residues and other lignocellulosic biomass. Five genes, encoding L-arabinose isomerase (araA), L-ribulokinase (araB), L-ribulose-5-phosphate-4-epimerase (araD), transaldolase (talB), and transketolase (tktA), were isolated from Escherichia coli and introduced into Z. mobilis under the control of constitutive promoters that permitted th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
56
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 196 publications
(57 citation statements)
references
References 20 publications
0
56
0
1
Order By: Relevance
“…Again, we found that improved xylose transport led to improved xylose fermentation performance, confirming our previous results. Previous reports have also predicted that sugar transport is a limiting factor in arabinose fermentations by Z. mobilis (Deanda et al, 1996). The Glf protein likely transports this sugar into the cell, but the affinity of Glf for arabinose is much lower than its affinity for other sugars, including glucose and xylose (Weisser et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…Again, we found that improved xylose transport led to improved xylose fermentation performance, confirming our previous results. Previous reports have also predicted that sugar transport is a limiting factor in arabinose fermentations by Z. mobilis (Deanda et al, 1996). The Glf protein likely transports this sugar into the cell, but the affinity of Glf for arabinose is much lower than its affinity for other sugars, including glucose and xylose (Weisser et al, 1996).…”
Section: Discussionmentioning
confidence: 95%
“…Therefore, d-xylose is converted to d-xylulose 5-phosphate through d-xylulose (Gu et al, 2010;Kawaguchi et al, 2006). For the utilization of l-arabinose, a group of three genes, araB (ribulokinase), araA (l-arabinose isomerase), and araD (l-ribulose phosphate 4-epimerase), is necessary, which mediates the conversion of l-arabinose though l-ribulose and l-ribulose 5-phosphate to d-xylulose 5-phosphate (Deanda, Zhang, Eddy, & Picataggio, 1996;Xiong, Wang, & Chen, 2016). This araBAD operon has been successfully integrated and heterologously expressed in C. glutamicum (Kawaguchi, Sasaki, Vertès, Inui, & Yukawa, 2008) to enable its growth on l-arabinose.…”
Section: Introductionmentioning
confidence: 99%
“…Zymomonas mobilis is an attractive ethanologen for cost-competitive ethanol production in view of its high ethanol yield, rapid specific substrate uptake rates and high ethanol tolerance. For conversion of lignocellulosic raw materials to ethanol, broadening its substrate range has been achieved successfully with introduction of exogenous genes from Escherichia coli encoding the assimilation and metabolism of the pentose sugars xylose and arabinose [1,2]. Kinetic studies on these recombinant strains using either xylose or glucose/xylose media have established that the specific rates of xylose uptake were 2-3-fold lower than those for glucose [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%